STUDENT’S PERCEPTION TOWARDS FINANCIAL MANAGEMENT IN ENGLISH INSTITUTION COURSE - Viny Setiani; Riatul Farohah; Iman Santoso (IKIP Siliwangi, 2018)
Perspective in education has a role to evaluate the effectiveness of the teaching-learning process. This research was conducted to know the students’ perspective about teaching and learning process of Financial Management in English Institution course whether it effective or not. A sampling method was used to select the representative sample. To collect the data, this research used the questionnaire which showed the students’ perception of Financial Management Course. The result of the study indicated that Financial Management in English Institution course has the positive perspective from students, this is evidenced by the high positive percentage of each statement. According to the result, Financial Management in English Institution course is acceptable by the student, 68.35% students gave the positive perspective to this course even though the material has considerable differences with English education materials, it means that teaching and learning process of Financial Management course was effective. But 31.65% students gave negative perspective, it means that this course need improvement in many aspects and students can get the advantages of this course. Because financial management is also required in managing the finances of an institution including English education institutions, therefore students of English education also need to study this course.i